Analisis penerapan model four levers of control dalam meningkatkan kinerja karyawan divisi keuangan PT Pelabuhan Indonesia (Persero) Regional 4 Bitung - Jesicca Leonita Baramuli; Hendrik Manossoh; Sherly Pinatik (Yayasan Widyantara Nawasena Raharja, 2023)
Four Levers of Control is a concept that focuses on achieving strategies in the management control system using four frameworks consisting of belief systems, boundary systems, diagnostic control systems, and interactive control systems. In facing the changes that occurred at PT Pelabuhan Indonesia (Persero) Regional 4 Bitung after the merger, an adequate control system is needed to control the performance of employees. This study aims to determine how the application of the four levers of control in improving the performance of employees of the finance division of PT Pelabuhan Indonesia (Persero) Regional 4 Bitung. The research method used in this research is a qualitative method with a descriptive approach and the data obtained comes from interviews and documentation. The results showed that the application of the four levers of control has been running quite well because it has fulfilled the four frameworks.